Rare case of axillary lymph node metastasis in papillary thyroid carcinoma detected using Iodine-131 whole-body scintigraphy and single-photon emission computed tomography/computed tomography - Kamaleshwaran, Koramadai Karuppusamy (Indian J Nucl Med, 2015)
Differentiated thyroid cancer is, usually, associated with an excellent prognosis and indolent course. Distant metastases are rare events at the onset of thyroid cancer. Among these presentations, metastasis to the axillary lymph nodes is even more unusual. Only few cases of papillary carcinoma with axillary nodal metastasis were previously reported in the literature. We present a 38-year-old female who underwent Iodine-131 whole-body scintigraphy, after total thyroidectomy and bilateral neck lymph node dissection for papillary carcinoma of thyroid, showed intense uptake in the remnant thyroid, lung metastasis, left cervical and left axillary lymph nodes. Excision of left axillary lymph nodes confirmed metastatic papillary carcinoma.